NEGATIVE CORRELATION BETWEEN STOCK AND FUTURES RETURNS: AN UNEXPLOITED HEDGING OPPORTUNITY?. (14th June 2016) - Basu, Parantap; Gavin, William T.
ABSTRACT: The negative correlation between equity and commodity futures returns is widely perceived by investors as an unexploited hedging opportunity. A Lucas (1982) asset‐pricing model is adapted to analyse the fundamentals driving equity and commodity futures returns. Using the model we argue that such a negative correlation could arise as an equilibrium relationship which reflects traders' perceptions about the shocks driving the fundamentals such as energy and consumables, and does not necessarily indicate any hedging opportunity.